Pengaruh Tax Avoidance dan Capital Intensity terhadap Nilai Perusahaan dengan Kepemilikan Institusional sebagai Variabel Moderasi : (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023) - Claudia Mutiara Mina Azzahra; Jouzar Farouq Ishak; Dian Imanina Burhany; Arif Afriady (Jurusan Akuntansi Politeknik Negeri Bandung, 2026)
This study employs a descriptive quantitative method to examine the effect of tax avoidance and capital intensity on firm value, with institutional ownership as a moderating variable. The research focuses on manufacturing companies listed on the Indonesia Stock Exchange from 2019 to 2023. Tax avoidance is measured using the Effective Tax Rate (ETR), capital intensity by the Capital Intensity Ratio (CIR), and firm value by Tobin’s Q. The study uses secondary data from annual financial reports. Results show that tax avoidance has no significant effect on firm value, while capital intensity has a significant negative effect. Institutional ownership does not significantly moderate the relationship between tax avoidance and firm value, but significantly moderates the relationship between capital intensity and firm value in a negative direction. Overall, tax avoidance, capital intensity, institutional ownership, and their interactions have a joint significant effect on firm value.